2019
DOI: 10.1371/journal.pone.0218171
|View full text |Cite
|
Sign up to set email alerts
|

Minimal extrathyroidal extension affects the prognosis of differentiated thyroid cancer: Is there a need for change in the AJCC classification system?

Abstract: Minimal extrathyroidal extension (ETE) is defined as tumor cells extending to the sternothyroid muscle or perithyroidal soft tissue. However, there is controversy regarding whether the magnitude of ETE (minimal or gross) should be considered in assigning a precise TNM stage to patients with thyroid cancer in the seventh/eighth editions of the AJCC system. The present study evaluated Surveillance, Epidemiology, and End Results data from 107,114 patients with differentiated thyroid cancer (2004–2013) to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…Concerning the 10/30 (33.3%) patients who had mETE at surgery, it resulted that also this risk factor is associated with a poor prognosis (p = 0.027) and at the univariate analysis the affected patients showed an increased risk for metastasis appearance after thyroidectomy, OR 3.25 (95% CI 1.13-9.41), p-value = 0.03. These results referring to the few cases of the present study confirm previous data reported in the literature [9,[17][18][19][20][21] while differing from others [13,[22][23][24][25][26][27][28]. Moreover, the primary tumor size of mETE patients was >15 mm in 9/10 (90%) of cases and <10 mm in the remaining case, the latter being a microcarcinoma (8 mm).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Concerning the 10/30 (33.3%) patients who had mETE at surgery, it resulted that also this risk factor is associated with a poor prognosis (p = 0.027) and at the univariate analysis the affected patients showed an increased risk for metastasis appearance after thyroidectomy, OR 3.25 (95% CI 1.13-9.41), p-value = 0.03. These results referring to the few cases of the present study confirm previous data reported in the literature [9,[17][18][19][20][21] while differing from others [13,[22][23][24][25][26][27][28]. Moreover, the primary tumor size of mETE patients was >15 mm in 9/10 (90%) of cases and <10 mm in the remaining case, the latter being a microcarcinoma (8 mm).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, extrathyroid tumor extension (ETE) has been recognized as a prognostic factor of DTC [13,14]. However, while extended ETE (eETE) proved a significant worsening of the prognosis [13][14][15][16], the impact of minimal ETE (mETE) is controversial presenting an increased risk of recurrence in some studies [8,[17][18][19][20][21] and vice versa reporting no significant impact on disease-free survival in other studies [13,[22][23][24][25][26][27][28]. DTC has slow growth and recurrences and metastases can appear and become clinically evident even many years later; thus, the carcinomas can require a long-term follow-up to guarantee careful surveillance of the affected patients [10,29].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroidectomy with modified radical neck dissection is recommended for N1b patients with gross ETE (1,4). Those unfavorable events have been shown to correlate to poor prognosis of patients with thyroid carcinoma, evidenced by increasing recurrence rate at both resection site and regional lymph node, lowering the overall and disease-free survival (5)(6)(7)(8)(9). Accordingly, the influence of nodule size on the risks of those unfavorable events should be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, variables with significant prognostic power have been identified and employed to reach reliable classifiers by our preferred models, MLP-1 and MLP-2. On the other hand, MLP-3, which was generated based on the TNM tumour staging system was not able to predict survival (80.84%) nor death (81.40%) at the same rate as the other models, as its global accuracy is 13.6% and 10.2% lower than MLP-1 and MLP-2, respectively (Table 3), also supporting current limitations in thyroid cancer modelling based on AJCC guidelines 15 . It is worth mentioning that in the present research, a classification problem has been carried out to serve as a prognosis assessment.…”
Section: Discussionmentioning
confidence: 74%
“…We validated our network through a direct comparison to an ANN generated using the AJCC TNM staging system, further demonstrating the power of our artificial intelligence system when coupled with relevant clinical features. Consequently, we believe our findings reveal the need for change in current thyroid cancer assessment standards, coinciding with new studies in the field 15 .…”
mentioning
confidence: 58%